PENERAPAN PROBLEM BASED LEARNING DENGAN MENGGUNAKAN BAHAN AJAR BERBASIS ANDROID PADA MATERI BARISAN DAN DERET ARITMATIKA - M. Taufiq Qur Rahman; Hapizah Hapizah (Universitas Sriwijaya, 2021)
The purpose of this study was to see the attitude of independence and student learning outcomes after applying problem based learning (PBL) using Android-based teaching materials on arithmetic sequences and series material. This type of research is descriptive research. The research subjects were 35 students of class XI MIA 1 SMA Negeri 10 Palembang. The data collection techniques used were observation, questionnaires and written tests. The results of this study indicate that the independence of students after implementing PBL using Android-based teaching materials can be categorized as good, namely with an average of 82.76%. While student learning outcomes are categorized as good with an average value of 77.5